Rapid ethnographic assessment of the COVID-19 pandemic April 2020 'surge' and its impact on service delivery in an Acute Care Medical Emergency Department and Trauma Center. Issue 10 (20th October 2020) - Palinkas, Lawrence A; Whiteside, Lauren; Nehra, Deepika; Engstrom, Allison; Taylor, Mark; Moloney, Kathleen; Zatzick, Douglas F
Abstract : Objectives: Assess the impacts of the COVID-19 pandemic on service delivery by frontline healthcare providers in acute care medical and emergency department settings and identify strategies used to cope with pandemic-related physical and mental health demands. Design: Rapid clinical ethnography of patient–provider encounters during an initial pandemic 'surge' conducted by a team of clinician–researchers using a structured protocol for qualitative data collection and analysis. Setting: Level 1 trauma centre at Harborview Hospital in Seattle Washington in April 2020. Participants: Frontline clinical providers serving as participant observers during performance of their clinical duties recorded observations and summaries of conversations with other providers and patients. Results: We identified four different kinds of impacts: procedural, provider, patient and overall. Each impact highlighted two or more levels of a socioecological model of services delivery: (1) the epidemiology of COVID-19, (2) outer setting, (3) inner or organisational setting and (4) individual patient and provider. Despite significant changes in procedures that included COVID-19 screening of all admitted patients, social distancing and use of personal protective equipment, as well as changes in patient and provider behaviour, the overall impact of the pandemic on the emergency department and acute care service delivery was minimal. This is attributed to having a smaller surge than expected, a quick response by the healthcare system to anticipated demands for service delivery and protection of patients and providers, adequate supplies and high provider morale. Conclusions: Although limited to one setting in one healthcare system in one community, the findings offer some important lessons for healthcare systems that have yet to be impacted as well as systems that have been more severely impacted. Each of the socioecological framework levels was found to impact service delivery to patients, and variations at each of these levels account for variations in that quality of care globally.